Comparative study of pregnancy outcomes in women with inflammatory bowel disease treated with thiopurines and/or anti‐TNF: a French nationwide study 2010–2018. Issue 3 (23rd June 2021) - Meyer, Antoine; Drouin, Jérôme; Weill, Alain; Carbonnel, Franck; Dray‐Spira, Rosemary
Summary: Background: Data about thiopurines or anti‐TNF use during pregnancy in women with inflammatory bowel diseases (IBD) are reassuring. However, many studies are based upon small sample sizes. Aims: To assess IBD medication safety during pregnancy. Methods: Using the French national health database, which covers more than 99% of the French population, around 65 000 000 people, we identified pregnancies ending with a birth in IBD patients in France between 2010 and 2018. Pregnancy outcomes (vital status at birth, birth term, and weight for gestational age) were compared according to treatment exposure during pregnancy using propensity score‐weighted marginal logistic regression models. Results: 27 729 pregnancies were included: 3554 were exposed to thiopurines monotherapy, 3525 to anti‐TNF monotherapy, 839 to combination therapy, and 19 811 unexposed. Pregnancies exposed to thiopurines monotherapy compared to unexposed pregnancies more frequently resulted in stillbirths (1.0% vs 0.5%, aOR 2.04; 95%CI: 1.18‐3.55), preterm birth (12.3% vs 7.1%, aOR 1.76; 95%CI: 1.55‐2.00), large for gestational age (10.6% vs 8.4%, aOR 1.32; 95%CI: 1.13‐1.53) and less frequently in small for gestational age (9.6% vs 11.1%, aOR 0.79; 95%CI: 0.67‐0.92). By contrast, pregnancies exposed to anti‐TNF monotherapy were not different from unexposed pregnancies as regards to these outcomes. Compared to unexposed pregnancies, those exposed to combination therapy more frequently resulted in preterm births (aOR 1.55; 95%CI: 1.15‐2.11) and larger for gestational age (aOR 1.61; 95%CI: 1.13‐2.29) but did not differ as regards to stillbirths. Conclusions: Pregnancies exposed to thiopurines more frequently resulted in stillbirths, preterm births and large for gestational age compared to pregnancies exposed to anti‐TNF or unexposed pregnancies. By contrast, pregnancies exposed to anti‐TNF monotherapy were not associated with these outcomes. Abstract : Pregnancies exposed to thiopurines more frequently resulted in stillbirths, preterm births, and large for gestational age compared to pregnancies exposed to anti‐TNF or unexposed pregnancies. By contrast, pregnancies exposed to anti‐TNF monotherapy were not associated with these outcomes